Expressão imunoistoquímica de HER2 em adenocarcinoma do estômago na região central do Rio Grande do Sul - Carli, Diego Michelon de (2013)
Introduction: Worldwide, Gastric Cancer (GC) is the fourth cancer in incidence and the second most common cause of cancer death. Because it is asymptomatic in the early stages, it is often diagnosed in advanced stages. HER2 gene expression has been identified in about 20% of GC. Its expression is associated with a worse prognosis for GC patients. Objectives: To study HER2 immunoexpression in specimens of gastric adenocarcinoma and its association with histological classification and anatomical location. Patients and methods: We conduct a cross-sectional study, where we analyzed HER2 immunoexpression in 48 specimens of gastric adenocarcinoma. We use avidin-biotin method with primary antibody peroxidase C-erb B2, clone EP1045Y (Biocare Medical, USA). Results: We found seven positive cases. HER2 was expressed in 5 intestinal type and 2 in the intestinal component of mixed type. There was no expression of HER2 in diffuse type. HER2 expression was associated with the intestinal component of gastric adenocarcinoma (p = 0.003). Regarding the anatomical site, 1 in 6 (16.6%) proximal cases was positive for HER2, and 6 in 42 (14.28%) distal were positive for HER2. We did not find an association between HER2 expression and the anatomical site of GC. Conclusion: HER2 immunoexpression was found in 14.6% of the sample and it showed significant association with Lauren's intestinal subtype.